A comparison of dynamic cooperation clustering algorithms and pilot assignment methods on performance, complexity and fairness of user centric mimo uplink - Bigonha, Antonio Bittar (2024)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2024.